TINJAUAN ETNOMUSIKOLOGI TENTANG MAKNA DAN PERAN “KNOBE” DALAM MENJAGA IDENTITAS MUSIK TRADISIONAL TIMOR TENGAH SELATAN - Margarita D.I Ottu (LPPM Politeknik Saint Paul Sorong, 2025)
This study examines the cultural significance and functional roles of Knobe, a traditional bamboo instrument of the Atoin Meto’ community in Timor Tengah Selatan (TTS), through an ethnomusicological lens. As an indigenous musical practice, Knobe embodies not only aesthetic expression but also a complex web of social meanings, ritual functions, and symbolic relationships between humans, nature, and ancestral traditions. Using qualitative ethnographic methodsincluding observation, in-depth interviews, and documentation this research explores how Knobe operates within daily life, ritual ceremonies, and processes of intergenerational cultural transmission. The findings show that Knobe serves multiple cultural functions that as a medium for ritual communication, a tool for social cohesion, a vehicle for moral and historical education, and a marker of regional identity. Its acoustic characteristics, performance techniques, and repertoire reflect an intimate fusion of bodily technique, ecological knowledge, and cultural symbolism. Despite the pressures of modernization, Knobe continues to play a vital role in sustaining the musical identity and cultural continuity of the TTS community. This study highlights Knobe as both an artistic practice and a cultural archive that preserves collective memory, reinforces identity, and contributes to the broader discourse on safeguarding Indonesia’s intangible cultural heritage.